2003
DOI: 10.1080/1475636031000071826
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition ofTrypanosoma cruziα-Hydroxyacid Dehydrogenase-isozyme II by N-Isopropyl Oxamate and its Effect on Intact Epimastigotes

Abstract: The effect of N-isopropyl oxamate on the activity of alpha-hydroxyacid dehydrogenase-isozyme II (HADH-isozyme II) from Trypanosoma cruzi was investigated. The kinetic studies showed that this substance was a competitive inhibitor of this isozyme. The attachment of the nonpolar isopropylic branched chain to the nitrogen of oxamate increased 12-fold the affinity of N-isopropyl oxamate for the active site of T. cruzi HADH-isozyme II. N-isopropyl oxamate was a selective inhibitor of HADH-isozyme II, since other T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…It has been established that HADH-isozyme II is actually integrated into metabolic pathways supplying energy for the motility of flagellum and survival of the parasites [10], because this isozyme participates in the reoxidation of NADH during glycolysis [17], and in a shuttle system transferring reducing equivalents (NADH) from cytosol into the mitochondria [10]. Consequently, an inhibitor of HADH-isozyme II will not only inhibit glycolysis but will also inhibit the shuttle system, and therefore, it has been proposed that inhibitors of this isozyme could reduce the motility and survival of this parasite [5,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that HADH-isozyme II is actually integrated into metabolic pathways supplying energy for the motility of flagellum and survival of the parasites [10], because this isozyme participates in the reoxidation of NADH during glycolysis [17], and in a shuttle system transferring reducing equivalents (NADH) from cytosol into the mitochondria [10]. Consequently, an inhibitor of HADH-isozyme II will not only inhibit glycolysis but will also inhibit the shuttle system, and therefore, it has been proposed that inhibitors of this isozyme could reduce the motility and survival of this parasite [5,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…However, this compound did not show any activity when tested on V2R T. cruzi epimastigote culture, unless it was transformed in its prodrug, the ethyl ester of N -isopropyl oxamate (Et-NIPOx). Actually, it was even better than nifurtimox and benznidazol [ 58 ]. A hypothesis advanced to explain this effect was the existance of carboxylesterases, aliphatic or non-specific esterases, in T. cruzi epimastigotes [ 59 ].…”
Section: Antichagasic Prodrugsmentioning
confidence: 99%
“…Increased effectiveness of Et-NIPOx most probably resulted from their better absorption by this parasite and its efficient hydrolysis by carboxylesterases in situ into the active HADH inhibitor [ 58 ]. This was later also confirmed in vivo [ 60 ], when Et-NIPOx was tested on mice parasitaemia, exhibiting trypanocidal activity in the five tested T. cruzi strains.…”
Section: Antichagasic Prodrugsmentioning
confidence: 99%
“…However, when we tested the trypanocidal activity of NPOX and NIPOX, we were not able to detect any trypanocidal effect with these oxamates. In contrast, the corresponding ethyl esters (Et-NPOX and Et-NIPOX), acting as prodrugs, exhibited trypanocidal activity on cultured epimastigotes (in vitro) and murine trypanosomiasis (in vivo) in all the tested T. cruzi strains 8,14,15 . The increased effectiveness of Et-NPOX and Et-NIPOX resulted from their better absorption by this parasite and their efficient hydrolysis inside T. cruzi by its carboxylesterases 16,17 , generating the active HADH-isozyme II inhibitors and NIPOX in situ 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…In previous investigations we designed and synthesized N-propyl oxamate (NPOX) and N-isopropyl oxamate (NIPOX) as possible inhibitors of T. cruzi -hydroxyacid dehydrogenase (HADH)-isozyme II, and we found that these oxamates were indeed competitive and selective inhibitors of this isozyme (Figure 1) 7,8 . Since HADH-isozyme II participates in the energetic metabolism of T. cruzi [9][10][11] , a trypanocidal effect can be expected with these inhibitors 12,13 .…”
Section: Introductionmentioning
confidence: 99%